Crusted scabies complicated with herpes simplex and sepsis - Azizpour, Arghavan; Nasimi, Maryam; Ghanadan, Alireza; Mohammadi, Fariba; Shakoei, Safoura (Indian journal of dermatology, 2020)
Crusted scabies is a rare and extremely contagious infestation by Sarcoptes scabiei. Kaposi's varicelliform eruption (KVE) refers to herpes simplex virus infection superimposed on pre-existing dermatosis such as atopic dermatitis, Darier's disease, and pemphigus. We report a case of KVE superimposed on crusted scabies in a middle-aged woman. Her condition was complicated with sepsis. She was treated with IV meropenem, vancomycin, and acyclovir and was released 2 weeks later in good condition. To our knowledge, only rare cases of crusted scabies complicated by KVE have been reported.